Recurrent post-kala-azar dermal leishmaniasis. - Alborzi, A.; Ahanchin, A.R.; Karimi, A. (European Journal of Pediatric Dermatology, 2002)
An 11-year-old girl presented to our Department of Pediatrics with multiple nodules on her face. When aged one year, the patient suffered from kala-azar, treated with meglumine antimoniate (glucantime) 60 mg/kg per day for 4 weeks and completely recovered. At the age of five years she presented for the first time to our Pediatrics Infectious Ward with a few small skin nodules on her face and she was again treated with glucantime (60mg/kg per day) for 4 weeks and completely cured. At the age of nine years she developed diffuse skin nodules on her face. Smears from the lesions revealed Leishmania spp., leading us to again treat her with glucantime (60mg/kg per day) for 2 months with consequent disappearance of the nodules. When aged eleven years, she presented for the fourth time with diffuse skin nodules on her face leading us to treat her with glucantime (60mg/kg per day) plus allopurinol tablets (10mg/kg per day) for 2 months with excellent recovery.